2018
DOI: 10.3390/pharmaceutics10010020
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of (S)-Ketoprofen Co-Administered with Caffeine: A Preclinical Study in Arthritic Rats

Abstract: The purpose of the present study was to determine whether caffeine modifies the pharmacokinetics and pharmacodynamics of (S)-ketoprofen following oral administration in a gout-type pain model. 3.2 mg/kg of (S)-ketoprofen alone and combined with 17.8 mg/kg of caffeine were administered to Wistar rats and plasma levels were determined between 0.5 and 24.0 h. Additionally, antinociception was evaluated based on the protocol of the PIFIR (pain-induced functional impairment in the rat) model before blood sampling b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
8
0
4
Order By: Relevance
“…When ketoprofen is administered with caffeine, the values of C max and AUC were increased by 90.1% and 82.7%, respectively. The ketoprofen plasma concentrations were determined by HPLC analysis with ultraviolet (UV) detection [27].…”
Section: Effect On Absorption Bymentioning
confidence: 99%
See 4 more Smart Citations
“…When ketoprofen is administered with caffeine, the values of C max and AUC were increased by 90.1% and 82.7%, respectively. The ketoprofen plasma concentrations were determined by HPLC analysis with ultraviolet (UV) detection [27].…”
Section: Effect On Absorption Bymentioning
confidence: 99%
“…The most probable reason, according to the authors, is due to decreasing gastric pH, reducing gastric emptying, and increasing blood flow of the gastric mucosa effects of caffeine. In addition, coffee decreases the metabolic clearance of ketoprofen by decreasing the liver blood flow [27]. A study done on voluntary humans in Malaysia showed that there was an increase in the paracetamol rate and extent of absorption with coffee containing 65 and 195 mg of caffeine.…”
Section: Effect On Absorption Bymentioning
confidence: 99%
See 3 more Smart Citations